2023
DOI: 10.3390/ph16081154
|View full text |Cite
|
Sign up to set email alerts
|

Honey as a Natural Nutraceutical: Its Combinational Therapeutic Strategies Applicable to Blood Infections—Septicemia, HIV, SARS-CoV-2, Malaria

Abstract: Honey is a natural substance that has existed alongside humanity since the time of antiquity, acting then as a source of nutrition, as well as a source of medicinal aid for people. Ancient civilizations from multiple nations of the world, from ancient China to ancient Greece and Egypt, utilized the supposed healing properties of honey to treat lacerations and wounds, as well as for internal pathologies such as intestinal disease. At present, honey has entered the modern scientific research program in search of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…For this reason, this innovative approach could be extended to other airborne pathogens that affect plants, animals, and humans and could be used to predict recurrent outbreaks like seasonal influenza. Furthermore, as previously reported [72][73][74], it is important to underline that honey samples could also be used as further indicators of virus spread in the environment without causing harm to the consumer. However, this is a preliminary study, and it is necessary to conduct further studies on different territories to ensure the reliability of the data.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For this reason, this innovative approach could be extended to other airborne pathogens that affect plants, animals, and humans and could be used to predict recurrent outbreaks like seasonal influenza. Furthermore, as previously reported [72][73][74], it is important to underline that honey samples could also be used as further indicators of virus spread in the environment without causing harm to the consumer. However, this is a preliminary study, and it is necessary to conduct further studies on different territories to ensure the reliability of the data.…”
Section: Discussionmentioning
confidence: 92%
“…On the contrary, bibliographic studies have shown that for its antioxidant and antiinflammatory properties, it is even used to alleviate the clinical symptoms caused by SARS-CoV-2 by reducing the elimination time of the same virus [73,74]. Furthermore, Abedi et al (2021) evaluated the potential applications of honey and its constituent components as a possible treatment regime for COVID-19, and they have observed that the anti-inflammatory properties on proinflammatory cells and agents could lead to the prevention of SARS-CoV-2 penetration and reproduction in host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Honey is a natural nutraceutical and can be used in combinational therapeutic approaches [88] . Hydrogen peroxide has been reported as a potential wound therapeutic target [89] , in which the stabilization and controlled release of H 2 O 2 for wound treatment applications could be achieved through the use of micro-encapsulated hydrogen peroxide [90] .…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…have been identified for their possible application as therapeutic agents, that can be used for fortification of beverages for several health benefits including gut infections and disorders in the digestive system [ 90 , 91 ]. The bioactive compounds with antimicrobial and other therapeutic activities have been investigated in plant-sourced edible materials [ 92 , 93 , 94 , 95 , 96 ]. Products prepared using such bioactive materials are free from chemically synthesised molecules, for instance, commonly prescribed antibiotics have chemically-synthesised compounds.…”
Section: Conclusion and Emerging Trends In Nutraceutical Beveragesmentioning
confidence: 99%